Strategy of the Principal of Madrasah in Forming Students' Character at Madrasah Ibtidaiyah Al-Ijtihad Jontak - Mukhtar, Mukhtar (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study was conducted with the aim of finding out the strategy of the madrasah principal in forming the character of students at MI Al-Ijtihad Al-Mahsuni Jontak, as well as describing the supporting and inhibiting factors of the principal's strategy in forming the character of students at MI Al-Ijtihad Al-Mahsuni Jontak. This research is a qualitative research that is descriptive in nature, by trying to describe the research results obtained in the field. The types of data used in this study are primary and secondary data with data sources used consisting of the principal, teachers and students at MI Al-Ijtihad Al-Mahsuni Jontak with data collection techniques used by researchers in the form of observation, interviews and documentation. The data obtained are then processed in the form of words which are then poured into the form of descriptions or narratives. The results of this study are that the strategy of the madrasah principal in shaping the character of students, this can be seen from the improvement in the character of students after the madrasah principal implemented the strategies carried out to shape the character of students, students become students with good character. The supporting factors are the support and solidarity of teachers, staff and parents or guardians of students and teachers apply good ethics to other teachers so that they can be imitated by students. While the inhibiting factors are: lack of control by parents or guardians of students who use social media and environmental factors.